Early postoperative delirium after open-heart cardiac surgery is associated with decreased bispectral EEG and increased cortisol and interleukin-6 - Plaschke, Konstanze; Fichtenkamm, Philipp; Schramm, Christoph; Hauth, Steffen; Martin, Eike; Verch, Markus; Karck, Matthias; Kopitz, Jürgen (Intensive care medicine, 2010)
It is difficult to substantiate the clinical diagnosis of postoperative delirium with objective parameters in intensive care units (ICU). The purpose of this study was to analyze (1) whether the bilateral bispectral (BIS) index, (2) cortisol as a stress marker, and (3) interleukin-6 as a marker of inflammation were different in delirious patients as compared to nondelirious ones after cardiac surgery.